Production or transmission investments? A comparative study - Mario Blázquez de Paz (Research Institute of Industrial Economics (IFN), 2017)
A successful transformation to a carbon neutral energy system requires the correct investments in transmission and production capacity. In a zonal pricing electricity market, the one proposed by the European Commission to integrate the European electricity markets, I analyze the effects that investments in transmission and production capacity have on consumer welfare and suppliers' profits. In the specific setting of this paper, I show that when the competition is perfect, an investment in transmission capacity between zones (inter Transmission System Operator (TSO) investment) and an investment in production capacity generate the same equilibrium outcome allocations. In contrast, when the competition is imperfect, an inter TSO investment and an investment in production capacity generate different equilibrium outcome allocations.
Keywords: D43; D44; L13; L94; 330; electricity auctions; wholesale electricity markets; transmission capacity constraints; investment transmission capacity; investment production capacity; energy economics